1974
DOI: 10.1111/j.1365-2362.1974.tb02361.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acute Uraemia on Gluconeogenesis in Isolated Perfused Rat Livers

Abstract: Abetraet. The effect of acute uraemia on glucose and urea formation by isolated perfused liven of fasting rats was investigated.The basal gluconeogenesis following nephrectomy was significantly increased as compared to normal and sham operated controls. Enhanced glucose formation was associated with an increase in both urea synthesis and output of the p r l y metabolizable amino acids valine, leucine, and isoleucine. In the presence of a mixture of amino acids (serine, threonine, lysine, glutamic acid, ornithi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Normal, non-operated controls were omitted in the present experiments (perfusions with AIB excepted), as in previous studies no significant differences were found between these animals and sham-operated ones [8]. As has been shown previously in this and other laboratories, these animals quickly develop a severe uraemic syndrome* with an increase in urea and creatinine, the appearance of marked acidosis and a shift of the whole animal's metabolism towards a prevailing catabolic state [8, .…”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations
“…Normal, non-operated controls were omitted in the present experiments (perfusions with AIB excepted), as in previous studies no significant differences were found between these animals and sham-operated ones [8]. As has been shown previously in this and other laboratories, these animals quickly develop a severe uraemic syndrome* with an increase in urea and creatinine, the appearance of marked acidosis and a shift of the whole animal's metabolism towards a prevailing catabolic state [8, .…”
Section: Methodsmentioning
confidence: 85%
“…The sources of chemicals and animals have been described elsewhere [8]. [ 1 -14C ]a-aminoisobutyric acid (AIB) was purchased from New England Nuclear Corp. (Dreieichenhain) and was of more than 99% radiochemical purity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More complex adaptations than direct inhibition by substances circulating in uraemic serum must therefore account for these findings. Increased gluconeogenesis has also been reported in the isolated perfused livers of acutely uraemic rats (Frohlich, Scholmerich, Hoppe Seyler, Maier, Talke, Schollmeyer & Gerok, 1974).…”
Section: Discussionmentioning
confidence: 76%